Administration of hydro-alcoholic extract of spinach improves oxidative stress and inflammation in high-fat diet-induced NAFLD rats - Ali Amirinejad; Ali Saneei Totmaj; Farzaneh Mardali; Azita Hekmatdoost; Hadi Emamat; Majid Safa; Farzad Shidfar (BMC, 2021)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide. The aim of this study was to evaluate the effects of hydro-alcoholic extract of spinach (HES) on hepatic and serum measurements of NAFLD in a rat model. Methods In the prevention phase, 18 Sprague-Dawley rats were fed a high-fat diet, a high-fat diet plus 400 mg/kg HES, or a chow diet for seven weeks. For the treatment phase, after the induction of NAFLD, they were fed a high-fat diet, a high-fat diet plus 400 mg/kg HES, a chow diet, or a chow diet plus 400 mg/kg HES for four weeks (n = 6). Results Administration of HES combined with high-fat diet in rats was associated with decreased food intake (P < 0.01), weight loss (P = 0.01), and increased superoxide dismutase (SOD) (P = 0.02) enzyme activity in the liver, at the end of the prevention phase. hs-CRP (P < 0.05), PTX-3 (P < 0.05), and TNF-α (P < 0.05) gene expression in the liver were decreased and PPAR-γ (P < 0.05) gene expression in the liver was increased by spinach intake, both in the prevention and treatment phases. Furthermore, administration of spinach in the treatment phase increased serum TAC (P = 0.03) and hepatic GPX (P = 0.01) enzyme activity. Conclusion Taking into account the potential beneficial effects of HES on prevention and treatment of NAFLD in the present study, to confirm these findings, we propose that further clinical trials be conducted on human subjects with NAFLD.